STRATEGI KOMUNIKASI RIAU RHTYM CHAMBERS INDONESIA DALAM MEMPROMOSIKAN CALEMPONG KAMPAR PROVINSI RIAU - Dhwiky Suryaner Putera; Nurjanah " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Along with the erosion of indigenous culture and music as calempong Kampar Riau Province, causing some of the music group's desire to exhume and promote it, such as one conducted Riau Indonesia Rhtym Chambers. Chambers Rhtym Riau Indonesia stood on June 17, 2001, with a 9 personnel. Chambers rhtym Riau Indonesia heavily promoting calempong Kampar with packaged with the album "Sound of Svarnadvipa" containing material calempong Kampar. Therefore, this study aims to determine the Communication Strategy Rhtym Chambers Riau Indonesia In Promoting Calempong Kampar in Riau Province. This study uses descriptive qualitative research, with the selection of informants using purposive, consisting of one chairman and composers Riau Rhtym Chambers Indonesia, the personnel, 2 Management team Riau Rhtym Chambers premises and 2 music fans Riau Rhtym Chambers Indonesia and society general who has been following the development of Riau Indonesia Rhtym Chambers. Data collection techniques using observation, interviews, and documentation. For the data analysis, refer to the interactive model of Miles and Huberman. For checking the validity of the data using the extension of participation and triangulation techniques. The results of this study indicate Riau Indonesia Rhtym Chambers, the first in the strategy of targeting the audience by finding out who the target in order to establish an appropriate message. Second, in the delivery of this message Rhtym Chambers Riau Indonesia always carry cultural messages to the preservation and development of native culture Riau province that is based on direct observation of the obvious originality. Third, in determining methods Rhtym Chambers Riau Indonesia not only promotes well as providing information, education and to persuade the general public to Calempong Kampar. Fourth, Riau Indonesia Rhtym Chambers also use social media (instagram, twitter, facebook, youtube and I-Tunes), print media (newspapers) in order to promote calempong Kampar. Keyword : Communication Strategy Group Music Rhtym Riau Indonesia Chambers In Promoting The Music In Riau Province Calempong Kampar